2021
DOI: 10.1088/1361-6595/ac3e7f
|View full text |Cite
|
Sign up to set email alerts
|

Plume neutralization of an ionic liquid electrospray thruster: better insights from particle-in-cell modelling

Abstract: Ionic liquid electrospray thrusters with high specific impulse, high thrust accuracy and low thrust noise are very promising for space gravitational wave detection missions. The plume which may lead to surface charging of solar panels and sensitive spacecraft components is a great concern for the applications of electrospray thruster. Therefore, this paper investigates the plume neutralization process of the ionic liquid electrospray thruster through fully kinetic Particle­in­cell simulations. The unipolarity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…The coupling of these oscillations has significant impact on the performance of the RF biased system, such as the periodic change of thrust in figure 8. Similar phenomena of plasma oscillations are also observed in the alternate extracted beam of oppositely charged ions of a gridded iodine ion thruster [28] and plume neutralization of an ionic liquid electrospray thruster [55]. In the alternative extracted beam, the ion density and plasma potential distribution in phase space indicate typical oscillations of the charged ions due to the periodically alternating extraction and acceleration of oppositely charged ions.…”
Section: Electron Energysupporting
confidence: 60%
“…The coupling of these oscillations has significant impact on the performance of the RF biased system, such as the periodic change of thrust in figure 8. Similar phenomena of plasma oscillations are also observed in the alternate extracted beam of oppositely charged ions of a gridded iodine ion thruster [28] and plume neutralization of an ionic liquid electrospray thruster [55]. In the alternative extracted beam, the ion density and plasma potential distribution in phase space indicate typical oscillations of the charged ions due to the periodically alternating extraction and acceleration of oppositely charged ions.…”
Section: Electron Energysupporting
confidence: 60%
“…Wang et al [32][33][34] performed Particle-in-Cell (PIC) simulations to investigate the plume in spatial distribution and found that the bipolar ion beam was almost uncoupled, and the plume exhibited no backflow. Zhang et al [35] conducted PIC simulations of the plume in spatial distribution and observed that self-neutralization of the plume is achieved through temporal and spatial oscillations of the ion beam. The spatial distribution of the plume demonstrates strong self-neutralization effectiveness and is relatively easier to achieve compared to temporal distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers describe the self-neutralization effectiveness of plumes mainly by comparing the potential and electric field strength at specific points or lines in space, however, there is a lack of a precise definition of the self-neutralization effectiveness of the plume. Wang and Zhang et al compared the spatial electrode potentials of bipolar and unipolar plumes by examining cross-sections in various x or y directions [32,35]. On the other hand, Oudini recorded the charging effect of the plume at a specific point located 5 cm downstream in the 50 × 5 cm space [36].…”
Section: Introductionmentioning
confidence: 99%
“…It plays a significant role in various problems, such as plasma plume expansion [2,3], particle-beam interactions [4], plasma instabilities [5,6], and inertial electrostatic confinement fusion [7]. Many types of simulation methods for solving the Vlasov-Poisson equation have been developed, such as the fully kinetic particle-in-cell (PIC) method [8][9][10][11][12], the semi-Lagrangian method [13][14][15][16], and the Eulerian method [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%